Perceived Barriers and Benefits of Exercise Among Men with Histories of Sexual Violence: Impact of PTSD and Physical Activity Status - Pebole, Michelle M. (Journal of interpersonal violence, 2023)
This study reported on perceived benefits and barriers of exercise among men with histories of sexual violence (SV) and compared these perceptions by activity level and post-traumatic stress disorder (PTSD) status. An online, cross-sectional, survey of men with histories of SV (N = 198) was completed using Amazon Mechanical Turk. Inclusion criteria were identifying sex at birth as male, age between 18 and 65 years, self-reported history of SV, and living in the United States (U.S.). A total of 1,260 men were screened for the study, of which 316 met the inclusion criteria, and 198 met all data quality requirements and were included in the study. Sociodemographic information, exercise behavior, PTSD symptoms, and perceived exercise barriers/benefits were collected. Comparisons by activity and PTSD status were analyzed. Additionally, two open-ended qualitative research questions were included to provide nuance to perceived barriers/benefits of exercise. The most salient benefits included physical performance, psychological outlook, and preventative health. Open-ended responses also noted the mental and physical benefits of exercise. The most salient barrier was physical exercise, with open-ended responses emphasizing lack of time, chronic pain and health concerns, and poor mental health and lack of motivation as impediments to exercise. Significant differences were found in benefits (psychological outlook, physical performance) and barriers (exercise environment, high time expenditure, and family discouragement) between active and insufficiently active men with histories of SV (ps < .05; Cohen’s ds = 0.32–0.57). Significant differences were found by PTSD status on benefits (physical performance, social interaction, and preventative health) and barriers (exercise milieu, time expenditure, hard physical exercise, family discouragement) (ps < .05; Cohen’s ds = 0.40–1.10). Findings provide new gender-specific strategies for promoting exercise among men with histories of SV: integrating exercise physiologists into trauma recovery programs, psychoeducation, engaging friends and family members, peer-support, and building self-efficacy.